Effects of maternal stress during different periods of pregnancy on the early neurobehavioral response of rats - Kvarik, Timea (2016)
Background: Several studies focus on the effects of prenatal stress in adulthood. Relatively little is known about the early neurodevelopmental consequences of such experiences and their predictive value. Thus we examined the early neurobehavioral responses of offspring whose mothers were exposed to restraint stress. Methods and results: Pregnant rats were exposed to 60 minutes restraint stress twice a day for seven days in different periods of pregnancy (early/mid and late phase). After birth, offspring were examined for the maturation of neural signs and reflexes daily for 3 weeks. Mid-pregnancy stress resulted in a subtle faster development in the appearance of eyelid and auditory startle reflexes, and in the disappearance of crossed extensor reflex. Pups exposed to stress in the last week of intrauterine life displayed a delay in air righting and showed a slight enhancement in the appearance of auditory startle. Conclusion: Based on our present findings, the deleterious consequences of prenatal stress are not apparent during the early developmental stages at least not detectable with the battery of test most widely used to examine neurobehavioral development. However, these findings draw the attention of the need of careful awareness in later ages in spite of the normal neurobehavioral development of newborns exposed to prenatal stress.